2004
DOI: 10.1128/jb.186.9.2682-2691.2004
|View full text |Cite
|
Sign up to set email alerts
|

LuxS-Mediated Signaling inStreptococcus mutansIs Involved in Regulation of Acid and Oxidative Stress Tolerance and Biofilm Formation

Abstract: LuxS-mediated quorum sensing has recently been shown to regulate important physiologic functions and virulence in a variety of bacteria. In this study, the role of luxS of Streptococcus mutans in the regulation of traits crucial to pathogenesis was investigated. Reporter gene fusions showed that inactivation of luxS resulted in a down-regulation of fructanase, a demonstrated virulence determinant, by more than 50%. The LuxS-deficient strain (TW26) showed increased sensitivity to acid killing but could still un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
251
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(274 citation statements)
references
References 48 publications
(76 reference statements)
22
251
1
Order By: Relevance
“…mutans strains were allowed to adapt and grow in BHI adjusted to pH 5.0 for 1 h before being subjected to acid killing (Wen & Burne, 2004). The results showed that like wild-type UA159, the BrpB-deficient mutant, JB409, also significantly increased its survival rate after 1 h incubation in BHI adjusted to pH 5.0 (Fig.…”
Section: Deficiency Of Brpb Causes Major Growth Defects In Strep Mutansmentioning
confidence: 87%
See 3 more Smart Citations
“…mutans strains were allowed to adapt and grow in BHI adjusted to pH 5.0 for 1 h before being subjected to acid killing (Wen & Burne, 2004). The results showed that like wild-type UA159, the BrpB-deficient mutant, JB409, also significantly increased its survival rate after 1 h incubation in BHI adjusted to pH 5.0 (Fig.…”
Section: Deficiency Of Brpb Causes Major Growth Defects In Strep Mutansmentioning
confidence: 87%
“…For field emission-scanning electron microscopy (FE-SEM) analysis, Strep. mutans overnight cultures were grown in BMG, BMGS or BMS on HA discs that were placed horizontally in 24-well plates as described elsewhere (Bitoun et al, 2011;Wen & Burne, 2004). After 24 h of growth, the HA discs were removed and washed twice with PBS, pH 7.4, before overnight fixation with 2.5 % glutaraldehyde (Polysciences) at 4 uC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genomes of many bacterial species, notably Escherichia coli, Salmonella enterica serovar Typhimurium, Shigella flexneri, Proteus mirabilis, Vibrio cholerae, Vibrio vulnificus, Campylobacter jejuni, Porphyromonas gingivalis, Bacillus subtilis, Streptococcus pyogenes, Streptococcus mutans, Clostridium perfringens and Clostridium difficile, include luxS homologues. In several of these, luxS-related AI-2 signals are involved in bacterial characteristics such as biofilm formation (Balestrino et al, 2005;Blehert et al, 2003;Fong et al, 2001;Wen & Burne 2004), flagella and motility (Jeon et al, 2003;Schneider et al, 2002;Stroeher et al, 2003), type III secretion systems (Sperandio et al, 1999), toxin production (Ohtani et al, 2002) and virulence (Lyon et al, 2001; Parsonnet et al, 1991;Stroeher et al, 2003).Helicobacter pylori has been identified as the aetiological agent of chronic active gastritis, peptic ulcer disease (Blaser, 1992;Graham, 1989), gastric adenocarcinoma (Parsonnet et al, 1991) and mucosal-associated lymphoid tissue (MALT) lymphoma (Wotherspoon et al, 1993). H. pylori has flagellar motility and is able to move through the Matsumoto et al, 1997;Yokota et al, 1991).…”
mentioning
confidence: 99%